DEVELOPMENT OF LEADING ECONOMIC SECTORS IN SERANG REGENCY - Syaifudin, Rizal; Sari, Titis; Desmawan, Deris; Adawiyah, Robi’ah (Management Science Research Journal, 2022)
This study was conducted with the aim of determining the unggualan sector in Serang Regency by usinglocation quotien (LQ) analysis and Shift Share analysis. The data that the researchers used was secondary data, this data was obtained from the Central Statistics Agency (BPS) of Serang Regency and the Central Statistics Agency (BPS) of Banten Province. The year period carried outfor this study started from 2016 to 2021. the results obtained from the Location Quotien (LQ) were obtained that soktors who have potential are in the Agriculture, forestry, and fisheries sectors with an average value of LQ 1.58; For the manufacturing sector, it has an average of LQ 1.44; for the Government Administration, Defense, and Compulsory Social Security sectors, it gets an LQ result of 1.09; and the Education sector, the average LQ result is 1.05. Meanwhile, the results of the Shift Share forthe leading sectors are the Manufacturing Industry Sector, the Construction Sector, the Large Trade and Retail Sector, the Car and Motorcycle Repair Sector, and the Agriculture, Forestry and Agriculture Sectors.